COVID-19 Pandemic, Geospatial Information, and Community Resilience : Global Applications and Lessons. - Rajabifard, Abbas; Paez, Daniel; Foliente, Greg. (Milton : Taylor & Francis Group, 2021)
Understanding pandemic resilience requires input from different disciplines. This book, with worldwide contributions examining the COVID-19 pandemic, provides interdisciplinary analysis and multi-sector expertise on the use of geospatial information and location intelligence to support community resilience and the management of pandemics.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books